\(36\div\left[7.\left(x-3\right)+4\right]=6\)
\(\Rightarrow7.\left(x-3\right)+4=36\div6\)
\(\Rightarrow7.\left(x-3\right)+4=6\)
\(\Rightarrow7.\left(x-3\right)=6-4\)
\(\Rightarrow7.\left(x-3\right)=2\)
\(\Rightarrow x-3=2\div7\)
\(\Rightarrow x-3=\frac{2}{7}\)
\(\Rightarrow x=\frac{2}{7}+3\)
\(\Rightarrow x=\frac{23}{7}\)
\(36:\left[7.\left(x-3\right)+4\right]=6\)
\(7.\left(x-3\right)+4=36:6\)
\(7.\left(x-3\right)+4=6\)
\(7.\left(x-3\right)=6-4\)
\(7.\left(x-3\right)=2\)
\(x-3=2:7\)
\(x-3=\frac{2}{7}\)
\(x=\frac{2}{7}+3\)
\(x=\frac{23}{7}\)